(untitled) (Neliniini Kolyvannya, 2025)
We obtain conditions for the existence and uniqueness of a positive piecewise continuous almost periodic solution to the equation of neoclassical growth model with almost periodic coefficients and impulse action at state-dependent moments. Solutions from some bounded set are attracted as t → ∞ to this almost periodic solution.